Rediscovery and distribution of Thor's fritillary Boloria thore (Hübner, 1803) (Lepidoptera: Nymphalidae) in Slovenia - Verovnik, Rudi (Acta entomologica slovenica (Ljubljana), 2020)
Thor's Fritillary (Boloria thore) has been considered extremely rare and localised at the south-eastern edge of its distribution in the Alps, especially in Slovenia. Despite surveys focused on sites with historical records (Julian Alps, Karavanke Mts.), there is almost a century long gap with no observations. Its discovery on the south-eastern slopes of Mt. Košuta (Karavanke Mts.) in 2004 was therefore unexpected, however within the known historical range of the species in the region. Since its rediscovery, the species has been observed at several new localities in the Karavanke Mts. and Julian Alps. These records are presented and habitat requirements as well as potential threats for the species are discussed.
Keywords: Boloria thore; butterflies; endangerment; habitat; Insecta; Lepidoptera; Metulji; montane species; montanske vrste; Nymphalidae; ogroženost; Papilionoidea; Slovenia; življenjski prostor; Žuželke